Banditry and Insecurity in Pastoral Kenya : A Critical Discourse (International Journal of Scientific Research in Science and Technology, 2025)
Banditry and protracted inter-ethnic conflicts resulting from Scarce resources, poverty and lack of economic opportunity have been stoking insecurity in pastoral Kenya since independence in 1963. Modern-day banditry has been commercialized over time and other actors including politicians and unscrupulous business men use it as triggers to instigate conflict to divert the attention of security agencies. The colonial government enforced the isolation of most of the Northern Frontier Districts (NFD) and North Western Kenya by enacting a series of Ordinances between the years 1901 to 1933 that systemically isolated and marginalized communities from this geographical area. Post-independence Kenyan authorities also felt there was a need to subject these communities to screening, profiling, and overregulation in these areas in comparison to the rest of the nation where the Presidency was granted the power to govern these communities by decree. This paper discusses the dynamics, enablers and drivers of banditry and insecurity in pastoral areas in Kenya.